Preparation and properties of triethyl citrate plasticized chitosan‐based membranes for efficient release of curcumin. Issue 14 (15th November 2021) - Huo, Li; Wei, Yuru; Zhang, Haixia; Wang, Ying; Deng, Bo; Wang, Yaxiong; Jin, Li'e
Abstract: In order to improve the release efficiency and physical properties of single polysaccharide membranes, two types of curcumin (Cur)‐loaded composite membranes have been successfully prepared through chitosan (CS)/carboxymethyl cellulose (CMC), CS/soluble starch (SS) with triethyl citrate (TEC) as a plasticizer. The structure and properties of the membranes were characterized by infrared spectroscopy, scanning electron microscopy, X‐ray diffraction, and thermogravimetry. The results of mechanical tests and drug release experiments show that TEC changes the intermolecular forces in the membrane matrix, makes the membrane more flexible and increases the cumulative release rate of curcumin. The cumulative release rate of Cur in CS/CMC‐Cur and the CS/SS‐Cur membrane can reach 86.5% and 87.3% at 24 h, respectively. Cur release in CS/CMC‐Cur followed the irregular Fickian diffusion behavior, whereas in CS/SS‐Cur followed the non‐Fickian diffusion behavior. The prepared composite membrane performs good thermal stability, tensile resistance and strong inhibitory effect on Escherichia coli . Abstract : Possible mechanism models of composite membranes releasing curcumin